DRAGONFLIES DIVERSITY AND LAND COVER CHANGES IN THE BATUBOLONG RIVER, WEST LOMBOK DISTRICT - Muhammad Zulhariadi; Raden Dedi Irawan; Aulia Zulfaeda; Nurul Hidayani (SEAMEO BIOTROP, 2022)
West Lombok District is the second largest district in Lombok Islands. The diversity of dragonflies (Order Odonata) as a bioindicator of environmental quality has not been widely studied in the West Lombok region. This study aimed to determine the species diversity of dragonflies (Order Odonata) found in Batubolong River, West Lombok District and its relation to the occurring land cover changes. This study was carried out by using a descriptive explorative method, where the sampling technique was done by means of line transects. Maps of study and sampling locations as well as land cover changes were made using ArcGIS 10.4.1 software based on primary and secondary data. The results showed that there were 11 species of dragonflies with a Shannon-Wiener diversity index value (H') of 2.212 (medium diversity), a population density index (C) of 0.126 (low dominance), and a species evenness index (E) of 0.923 (high uniformity). Our study also found two rare species of dragonfly in Lombok Island i.e., 3 individuals of Nososticta emphyla (Lieftinck, 1936) with 9% relative abundance and 1 individual of Drepanosticta berlandi (Lieftinck, 1939) with 3% relative abundance. The discovery of D. berlandi in Lombok is the third time after the findings in 1896 and the 19th century. Analysis of satellite data around the sampling area within the period 2013-2020 showed that there has been an increase in land cover of 6,149.29 m2. The increase in land cover changes may have caused the disappearance of several Odonata species in the sampling location.